Cumhuriyet sonrası Türkiye’ de eğitim gazeteciliği - Demirci Caferler, Nazmiye (My University, 2002)
Bu araştırmada, Cumhuriyet sonrasından günümüze çeşitli gazetelerin eğitim olaylarındaki tavırları incelenmiştir. Cumhuriyet'ten günümüze basın tarihimizi dört önemli döneme ayırarak, çalışma yapılmıştır. Her dönem içinde oluşan önemli eğitim olaylarının, basında eğitim haberi olarak yansıması incelenmiştir. Bu amaçla, ulusal basından farklı hedef kitlelere sahip gazetelerin arşivleri araştırılmıştır. Tek partili dönemde, eğitim reformlarının gazeteler tarafından desteklendiği görülmüştür. Eğitim sorunları sürekli gündemde tutulmuş, eğitim yenilikleri kamuoyuna duyurulmuştur. Çok partili döneme geçiş ile birlikte, gazetelerin eğitim haberlerinde de siyasal görüşlerden bağımsız hareket etmedikleri görülmüştür. Bunun en güzel örneği, '8 yıllık kesintisiz eğitim kanunu' hakkında gazetelerimizde çıkan haberlerdir. İncelenen gazete haberlerinden de görülmektedir ki; eğitim haberlerinde de gazeteler taraf tutmakta ve eğitim sorunlarını gündeme getirmek yerine, siyasal nitelikte olan eğitim haberlerini taraf tutarak yayınlamaktadırlar.

In this research paper, it has been tried to explain how some of the newspapers have seen the educational issues from the early days of the Republic until nowadays. The history of our press from the declaration of the Republic until today has been divided into 4 important periods and the research has been done accordingly. For each period , research has been focused on the projections of the important educational issues in press. To be able to do this, archives of the national newspapers with different reader groups has been searched. During the single party period, it has been seen that the educational reforms were supported by the newspapers. The problems of education were kept on the agenda and the educational renovations were announced to the public. After multiple number of parties started to act on the political arena, the educational news on the newspapers were not independent of the political views of those newspapers.A very good example of this are the articles about the law of 8-year compulsory education. Having searched the educational articles it has been clearly seen that the educational news in the papers have been having sides and instead of bringing the problems of education on the agenda the newspapers publish educational news which have subjective political implications.
Keywords: Gazetecilik Türkiye